Microbial transformation of ethynodiol diacetate - Mohd Sakre, Nurhanisah (2015)
The studies on microbial transformation have been well established as an important tool for the modifications of highly complex structure like steroids. Primarily, it can be used to synthesize chemical structure that might be difficult to obtain synthetically. Currently, research has been focused on structural modifications of bioactive steroids by using various microorganisms in order to obtain biologically potents compound with diverse structure. In this study, ethynodiol diacetate has been used as a substrate and undergone fermentation with nine selected endophytes. High Performance Liquid Chromatography (HPLC) has been performed to identify the biotransformed products.